2017
DOI: 10.28991/cej-2017-00000070
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PSO-ANN Model for Rainfall-Runoff Response in Basins, Case Study: Karaj Basin

Abstract: Successful daily river flow forecasting is necessary in water resources planning and management. A reliable rainfall-runoff model can provide useful information for water resources planning and management. In this study, particle swarm optimization algorithm (PSO) as a metaheuristic approach is employed to train artificial neural network (ANN). The proposed PSO-ANN model is applied to simulate the rainfall runoff process in Karaj River for one and two days ahead. In this regard, different combinations of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The results showed that the forecasting models are sensitive to different environmental input variables. AI-based models, especially ANN techniques, were frequently applied for forecasting purposes with streamflow and environmental processes thanks to easy implementation, low computational cost and suitable performance (Fotovatikhah et al, 2018;Motahari & Mazandaranizadeh, 2017;Olyaie, Banejad, Chau, & Melesse, 2015;Wang, Xu, Chau, & Lei, 2014;Zamanisabzi, King, Dilekli, Shoghli, & Abudu, 2018). They have been developed to predict a water quality index (Gazzaz, Yusoff, Aris, Juahir, & Ramli, 2012), monthly chemical oxygen demand concentration (Khalil, Awadallah, Karaman, & El-Sayed, 2012), daily water temperature, salinity and dissolved oxygen (Alizadeh & Kavianpour, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the forecasting models are sensitive to different environmental input variables. AI-based models, especially ANN techniques, were frequently applied for forecasting purposes with streamflow and environmental processes thanks to easy implementation, low computational cost and suitable performance (Fotovatikhah et al, 2018;Motahari & Mazandaranizadeh, 2017;Olyaie, Banejad, Chau, & Melesse, 2015;Wang, Xu, Chau, & Lei, 2014;Zamanisabzi, King, Dilekli, Shoghli, & Abudu, 2018). They have been developed to predict a water quality index (Gazzaz, Yusoff, Aris, Juahir, & Ramli, 2012), monthly chemical oxygen demand concentration (Khalil, Awadallah, Karaman, & El-Sayed, 2012), daily water temperature, salinity and dissolved oxygen (Alizadeh & Kavianpour, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of different machine learning techniques such as genetic algorithm, artificial neural network and fuzzy inference system into water quality have been reviewed by K.-W. Chau (2006). ANN and ELM models have been employed for water quality forecasting in rivers and seas (Alizadeh & Kavianpour, 2015;Dogan, Sengorur, & Koklu, 2009;Nodoushan, 2018;Tomić, Antanasijević, Ristić, Perić-Grujić, & Pocajt, 2018;Wu, Wang, Chen, Cai, & Deng, 2018), for DO concentration modeling (Heddam & Kisi, 2017), for river discharge monitoring (Garel & D'Alimonte, 2017;Motahari & Mazandaranizadeh, 2017) and for analysis of chlorophyll dynamics (Tian, Liao, & Zhang, 2017). Fotovatikhah et al (2018) provided a comprehensive survey on the computational intelligence applications in flood management systems.…”
Section: Introductionmentioning
confidence: 99%
“…PSO is a population-based stochastic optimization technique inspired by the social behavior of bird flocking (Motahari & Mazandaranizadeh 2017). In PSO, all particles have a fitness value, which is determined by the fitness function.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%